Mitchell, Queen, Mother, and Stateswoman: Mariana of Austria and the Government of Spain (Pennsylvania State Press, 2019) - Charles Beem (Royal Studies Journal, 2021)
Review of Sylvia Z. Mitchell, Queen, Mother, and Stateswoman: Mariana of Austria and the Government of Spain (University Park: Pennsylvania State Press, 2019).